2017
DOI: 10.1002/2017gc006822
|View full text |Cite
|
Sign up to set email alerts
|

Rock record and magnetic response to large earthquakes within Wenchuan Earthquake Fault Scientific Drilling cores

Abstract: Fault‐related pseudotachylytes are often considered to be produced by large seismic events. To investigate the rock record and magnetic response to large earthquakes within cores from the Wenchuan Earthquake Fault Scientific Drilling borehole 2 (WFSD‐2), we carried out microstructural, geochemical, and rock‐magnetic analyses of representative cores. Based on microstructural observations and powder X‐ray diffraction analyses, we found 21 layers of melt‐origin pseudotachylytes from 579.62 to 599.31 m‐depth in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…2A). Previous studies have found partially melted quartz in the WFSD-2 cores and surface outcrops along the Yingxiu-Beichuan fault (Wang et al, 2015;Zhang et al, 2017), suggesting that earthquakes with frictional heating temperatures above 1300 °C have occurred in the Longmen Shan thrust belt. The appearance of microlites at 1100 °C and 1300 °C shows that high temperatures are needed for the formation of microlites.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…2A). Previous studies have found partially melted quartz in the WFSD-2 cores and surface outcrops along the Yingxiu-Beichuan fault (Wang et al, 2015;Zhang et al, 2017), suggesting that earthquakes with frictional heating temperatures above 1300 °C have occurred in the Longmen Shan thrust belt. The appearance of microlites at 1100 °C and 1300 °C shows that high temperatures are needed for the formation of microlites.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, the formation of metallic iron during melting is another reason for the magnetic highs of pseudotachylyte. The Longmen Shan thrust belt has experienced earthquakes with high frictional melting temperatures (above 1300 °C) (Wang et al, 2015;Zhang et al, 2017); therefore, the metallic iron might be responsible for the magnetic highs of pseudotachylyte.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the presence of the glass is not a necessary feature of melt‐origin pseudotachylyte. Since a single seismic event is unlikely to produce multiple layers of pseudotachylytes with sharp boundaries (Shigetomi & Lin, ), the multilayered pseudotachylytes with different colors and thicknesses observed in the WFSD‐2 drilling cores (Zhang et al, ) should result from multiple seismic faulting events. Their different colors result from the different degrees of alteration, devitrification, or recrystallization in the different generations of pseudotachylytes (Lin, ).…”
Section: Discussionmentioning
confidence: 99%
“…The horizontal shear movement toward the crust has transformed into a brittle overthrust nappe movement away from the Minshan fault zone and the Longmenshan tectonic belt, resulting in a typical tectonic environment of reverse faults. The movement has also formed geophysical distortion zones, such as the Bouguer gravity anomaly and the aeromagnetic anomaly, and caused crustal thickness [71][72][73][74]. Due to the uplift of the Qinghai-Tibet Plateau and the further development of the original faults, some major faults, such as Minjiang fault, Beichuan-Yingxiu fault, and Pingwu-Qingchuan fault, have manifested strong tectonic activities [75,76].…”
Section: Geological Backgroundmentioning
confidence: 99%